Hypothermia reduction during neonatal transport in a tertiary care center in South India: a quality improvement initiative - Diggikar, Shivshankar; Shalet, Nirmala; S., Priya; Venkatagiri, Praveen (International Journal of Contemporary Pediatrics, 2021)
Background: Each degree drop in target temperature at admission increases mortality by 28% in neonates. Maintenance of target temperature during neonatal transport and at admission will pose an enormous challenge in developing countries due to various factors. The objective of the study was to decrease the incidence of hypothermia in transported babies at admission by 50% from a baseline of 64% over 12 months period. Prospective cohort study by QI methodology. Methods: Neonates transported to NICU from March 2019 – February 2020 were included. A baseline data was collected retrospectively to determine the incidence of existing hypothermic babies at admission. Problems were identified using Fishbone analysis. Evidence-based changes were implemented as per local needs in the Plan-Do Study cycle (PDSA) cycles. Results: A total of 96 babies were transported (62 babies during implementation, 34 during the sustenance Phase) during the study period. The mean (SD) gestation and birthweight was similar in the two groups. The distance travelled in kilometres in the hypothermic group was significantly more 7.3 (5.5) compared to the normothermic group 4.1(3.8) (p,0.01). We reduced the incidence of hypothermia from 64% to 16% over 12 months from the time of implementation. There was no correlation seen noted between hypothermia at admission and gestational age (r, - 0.18), birthweight (r, 0.04), or distance travelled in kilometres (r, 0.02). However, there was a positive correlation seen between adherence to the ‘5 Point -protocol’ and admission temperature (r, 0.86). Conclusions: Thermoregulation during neonatal transport is a huge challenge especially in the Indian scenario due to multiple incorrigible factors contributing to its high incidence even in the best of the centres. QI initiatives is a way forward to deal with some of these aspects. Involving the nursing team who forms the core team of neonatal transport is imperative.